A numerical analysis of the fracture toughness in phase‐field modelling of adhesive fracture. Issue 1 (15th March 2018) - Hansen‐Dörr, Arne C.; Hennig, Paul; Kästner, Markus; Weinberg, Kerstin
Abstract: We propose and analyse a phase‐field model which allows for adhesive interface failure between two materials by a local reduction of the critical fracture toughness over a given length scale in the vicinity of the interface. A parameter study is carried out which reveals a significant dependence of the cracking behaviour on the ratio between the length scale of the crack phase‐field model and the width of the adhesive interface. (© 2017 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)